9, 10-Phenanthrenequinone provokes dysfunction of brain endothelial barrier through down-regulating expression of claudin-5. (September 2021) - Kamase, Kyoko; Taguchi, Maki; Ikari, Akira; Endo, Satoshi; Matsunaga, Toshiyuki
Graphical abstract: Highlights: Among five DEP components, 9, 10-PQ provokes HBME cell toxicity most potently. The major cytotoxic mechanism of 9, 10-PQ is ROS-dependent apoptosis. Sublethal concentration of 9, 10-PQ raises permeability of the endothelial cell layer. The raised permeability may be due to the down-regulation of CLDN5 by ROS and NO. Abstract: Chronic exposure to diesel exhaust particle (DEP) is considered to provoke dysfunction of the blood-brain barrier, but the detailed molecular mechanism remains unclear. In this study, we investigated the toxic effects of five DEP components against human vascular cells and found that, among them, 9, 10-phenanthrenequinone (9, 10-PQ), a major tricyclic quinone in DEP, most potently elicits the cellular toxicities. Additionally, treatment with 9, 10-PQ at its cytolethal concentrations (more than 2 μM) facilitated the production of reactive oxygen species (ROS), caspase activation, and DNA fragmentation in human brain microvascular endothelial (HBME) cells, inferring that high concentrations of 9, 10-PQ elicit the cell apoptosis through the ROS-dependent mechanism. Measurement of trans-endothelial electrical resistance and paracellular permeability showed that treatment with sublethal concentrations (less than 1 μM) of 9, 10-PQ elevates permeability across HBME cell monolayer. Immunofluorescence observation and Western blotting analysis also revealed that the 9, 10-PQ treatment remarkably down-regulated the intercellular localization and expression of claudin-5 (CLDN5), a tight junctional protein that plays a key role in function of the blood-brain barrier, and the down-regulation was markedly recovered by pretreatment with a proteasome inhibitor Z -Leu-Leu-Leu-CHO. This result may indicate that sublethal concentrations of 9, 10-PQ facilitate the dysfunction of the endothelial cell barrier through lowering in the expression and proteasomal proteolysis of CLDN5. The treatment with 9, 10-PQ promoted nitric oxide (NO) production presumably through the induction of inducible NO synthase. In addition, the 9, 10-PQ-mediated down-regulation of CLDN5 was ameliorated and deteriorated by pretreating with a scavenger and donor, respectively, of NO. Similarly to the 9, 10-PQ treatment, treatment with a donor of peroxynitrite, a highly reactive oxidant formed by the reaction of NO and superoxide anion, resulted in the marked reduction of CLDN5 expression and elevation of 26S proteasome-based proteolytic activities. Thus, it is suggested that the formation of NO and peroxynitrite participates in the mechanism of brain endothelial cell barrier dysfunction elicited by 9, 10-PQ.